Detection and Analysis of Active Compounds in Ni gella sativa and Senna alata through Biological Methods - Shahla Hussien Hano (Peerian Journals Publishing, 2024)
The study is centered on compounds derived from Nigella sativa and Senna alata; extraction, identification and quantification methods of which are the focus of this study together with a focus on newer analytical techniques. These plants are known for their healing properties, namely, bactericidal, anti-inflammatory and anti-oxidative activity. The study seeks to observe these compounds with a view of determining their capacity in the creation of therapies
Keywords: Phytochemicals; Healing Herbs; Properties against Bacteria